One-Year Follow-Up of a Randomized Controlled Trial Piloting a Mindfulness-Based Group Intervention for Adolescent Insulin Resistance - Shomaker, Lauren B.; Pivarunas, Bernadette; Annameier, Shelly K.; Gulley, Lauren; Quaglia, Jordan; Brown, Kirk Warren; Broderick, Patricia; Bell, Christopher (Frontiers in Psychology, 2019)
Introduction To explore if a brief mindfulness-based intervention (MBI) leads to sustained, improved clinical outcomes in adolescents at-risk for type 2 diabetes (T2D). Methods Participants were 12–17y girls with overweight/obesity, elevated depression symptoms, and T2D family history participating in a randomized, controlled pilot trial of a six-session MBI vs. cognitive-behavioral therapy (CBT) group. At baseline and 1-year, mindfulness, depression, insulin resistance (IR), and body composition were assessed with validated instruments. Results One-year retention was 71% (n = 12) in MBI; 81% (n = 13) in CBT. At 1-year, depression decreased (Cohen’s d = 0.68) and IR decreased (d = 0.73) in adolescents randomized to MBI compared to those in CBT. There were no significant between-condition differences in mindfulness, adiposity, or BMI. Discussion One-year outcomes from this randomized, controlled pilot trial suggest that brief MBI may reduce depression and IR in at-risk adolescents. Replication and exploration of mechanisms within the context of a larger clinical trial are necessary. Clinical Trial Registration www.ClinicalTrials.gov, identifier NCT02218138.